Optimism &Amp; Pessimism: Implications for Theory, Research, and Practice. 2001
DOI: 10.1037/10385-012
|View full text |Cite
|
Sign up to set email alerts
|

Cultural influences on optimism and pessimism: Differences in Western and Eastern construals of the self.

Abstract: To be uncertain is to be uncomfortable, but to be certain is to be ridiculous.-Chinese ProverbIn recent years, psychologists have joined anthropologists, sociologists, and linguists in recognizing the role of culture in shaping human behavior

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
54
0
7

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(62 citation statements)
references
References 28 publications
1
54
0
7
Order By: Relevance
“…Optimism, in recent years, has been the subject of a great deal of attention as well was an extensive body of research (for reviews, see Chang 2001;Peterson 2000;Peterson and Bossio 1991;Scheier and Carver 1992;Seligman 1991;Snyder 1994;Taylor 1989). Measures of optimism have been shown to predict diverse and important benefits for individuals-positive mood (Weisse 1992), mastery-oriented achievement (Curry et al 1997;Peterson 1988), physical health (Kamen-Siegel et al 1991;Peterson 1988;Scheier and Carver 1987;Segerstrom et al 1998), and greater recovery from illness or surgery , to name but a few.…”
Section: Introductionmentioning
confidence: 99%
“…Optimism, in recent years, has been the subject of a great deal of attention as well was an extensive body of research (for reviews, see Chang 2001;Peterson 2000;Peterson and Bossio 1991;Scheier and Carver 1992;Seligman 1991;Snyder 1994;Taylor 1989). Measures of optimism have been shown to predict diverse and important benefits for individuals-positive mood (Weisse 1992), mastery-oriented achievement (Curry et al 1997;Peterson 1988), physical health (Kamen-Siegel et al 1991;Peterson 1988;Scheier and Carver 1987;Segerstrom et al 1998), and greater recovery from illness or surgery , to name but a few.…”
Section: Introductionmentioning
confidence: 99%
“…Dispositional optimism is one of the several theoretical perspectives that frame the construct of optimism as an individual difference (Carroll, Sweeny, & Shepperd, 2006;e. C. Chang, 2001a;Peterson, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…According to Peterson (2000), optimism is an inherent part of human nature that has made the growth of civilization possible, and so all contemporary cultures should possess a tendency to be generally optimistic. Nevertheless, Chang (2001) has shown that optimism and pessimism differ in Eastern and Western cultures. Peterson notes that desired outcomes are not universal; because cultures hold different primary goals and values, they are differentially optimistic about particular topics.…”
Section: Cultural Differences and Optimismmentioning
confidence: 99%
“…Variations in cultural values may result in differing assessments of environmental quality and optimism from nation to nation. As Chang (2001) asserts, "any model of optimism and pessimism that ignores the influence of culture is likely to be incomplete" (p. 276).…”
Section: Cultural Differences and Optimismmentioning
confidence: 99%